Historical fabulation; a framework to rethink the Islamic architecture outside Islamic world - Rashid, Md. Mizanur; Bartsch, Katharine (Archnet, MIT, United States, 2014)
The current study offers a critical interpretation of the more transient traces of Islam in Australia, and their representation in the equally scanty tangible evidences. The scope of recent surveys in this field is increasingly inclusive. However, very few studies focus on the architecture of Muslim communities in regions where Islam is not the predominant faith,especially in the southern hemisphere. The historical Adelaide Mosque, and many others, is excluded from the historical record despite the instrumental role it played in the life of Muslim settlers. This absence raises questions about gaps, or histories untold, as well as myths received, in histories of ‘Islamic’ architecture that raise questions about the truth - value of the past. There is a need to examine hybridized forms and shared architectural narratives to counter the myopic but persistent representation — or fabulation — of supposedly authentic, largely Arab - centric, forms of ‘Islamic’ architecture. This paper argues, then, that new theoretical frameworks are required to interpret this architectural hybrid that is, we argue, typical rather than exceptional.